Arched corridor in Saint Anne’s Church - Mumbai Archive Project Team (Jio Institute, 2024)
On July 31, 1887, coinciding with the Feast of Saint Ignatius Loyola, the founder of the Jesuits, Saint Anne’s was formally recognized as a parish. Saint Anne is traditionally believed to be the mother of the Virgin Mary, and the grandmother of Jesus.